Cisplatin-induced mesenchymal stromal cells-mediated mechanism contributing to decreased antitumor effect in breast cancer cells - Skolekova, Svetlana; Matuskova, Miroslava; Bohac, Martin; Toro, Lenka; Durinikova, Erika; Tyciakova, Silvia; Demkova, Lucia; Gursky, Jan; Kucerova, Lucia (Cell communication and signaling, 2016)
BACKGROUND: Cells of the tumor microenvironment are recognized as important determinants of the tumor biology. The adjacent non-malignant cells can regulate drug responses of the cancer cells by secreted paracrine factors and direct interactions with tumor cells. RESULTS: Human mesenchymal stromal cells (MSC) actively contribute to tumor microenvironment. Here we focused on their response to chemotherapy as during the treatment these cells become affected. We have shown that the secretory phenotype and behavior of mesenchymal stromal cells influenced by cisplatin differs from the naïve MSC. MSC were more resistant to the concentrations of cisplatin, which was cytotoxic for tumor cells. They did not undergo apoptosis, but a part of MSC population underwent senescence. However, MSC pretreatment with cisplatin led to changes in phosphorylation profiles of many kinases and also increased secretion of IL-6 and IL-8 cytokines. These changes in cytokine and phosphorylation profile of MSC led to increased chemoresistance and stemness of breast cancer cells. CONCLUSION: Taken together here we suggest that the exposure of the chemoresistant cells in the tumor microenvironment leads to substantial alterations and might lead to promotion of acquired microenvironment-mediated chemoresistance and stemness.
Keywords: Drug Resistance, Neoplasm; nádory prsu; apoptóza; cisplatina; Female; mezenchymální kmenové buňky; Cell Line, Tumor; Interleukin-8; Cisplatin; Apoptosis; ženské pohlaví; nádorové mikroprostředí; lidé; Breast; stárnutí buněk; Antineoplastic Agents; protinádorové látky; prsy; chemorezistence; Breast Neoplasms; Interleukin-6; Mesenchymal Stem Cells; interleukin-8; interleukin-6; Tumor Microenvironment; Cellular Senescence; nádorové buněčné linie; Humans